Pelatihan Aparat Desa dalam Menggunakan Statistik untuk Meningkatkan Pelayanan Publik di Desa Purworejo, Kecamatan Negeri Katon, Kabupaten Pesawaran, Provinsi Lampung - Mustofa Usman; Syarief Makhya; Riza Sawitri; Nonik Mega Sapitri; Edwin Russel (Pusat Riset dan Inovasi Nasional, 2025)
Purworejo Village, located in Negeri Katon, Pesawaran, has significant economic potential, especially in the agriculture and MSME sectors. However, its public services have not been fully integrated with adequate data systems, as the village apparatus still uses conventional methods in service delivery. Therefore, training for the village apparatus is needed to improve public services through the application of descriptive statistics. This training aims to equip village officials with basic data processing skills to enhance human resource capacity and promote better public service delivery. The training approach is participatory and practical, with participants not only receiving theoretical materials but also engaging in hands-on practice and case-based discussions relevant to village issues. The training results indicate that the use of descriptive statistics has significantly improved the understanding and skills of village officials in data processing for public services. The application of this method allows for more accurate, systematic, and easily understood information presentation, serving as a basis for targeted policy development.